Pendidikan Karakter di Sekolah Dasar: Tantangan dan Peluang di Era Modern - Ryfa Camila Maharani; Desty Endrawati Subroto; Az-Zahra Mutiara Fany; Ratu Siti Nurhasanah; Listiana Nova (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2025)
Character education in elementary schools plays a crucial role in shaping the morals and personalities of the younger generation, especially amidst the rapid development of technology and increasingly complex global challenges. This study aims to identify the challenges and opportunities in implementing character education through a qualitative descriptive approach via literature review. Based on the analysis of literature, including books, journals, and scientific articles, it was found that the main challenges in character education include the negative impact of technological advancements, social and economic inequality, lack of teacher training, and limited parental involvement. On the other hand, the modern era also presents significant opportunities, such as utilizing technology for interactive learning, integrating local, national, and global values through digital media, and fostering collaboration among schools, families, and communities. Additionally, the development of relevant and flexible curricula is also an important factor in supporting character education. Although the challenges are considerable, character education in elementary schools can be optimized by implementing innovative strategies, strengthening collaboration among various stakeholders, and wisely utilizing technology. This research offers recommendations to educators, policymakers, and the community to work together in supporting the achievement of character education goals, so that the younger generation can grow with integrity and adaptability to the changing times.